The Influence Of Agility, Cyberloafing Behavior, And Empowerment On Organizational Commitment With Work Stress As A Moderating Variable Among Employees In South Jakarta - Annisa Kharenina Augustine; Iwan Kresna Setiadi; Yudi Nur Supriadi (Dinasti International Journal of Education Management And Social Science, 2024)
This study aims to analyze the influence of agility, cyberloafing behavior, and empowerment on organizational commitment, with work stress as a moderating variable among employees working in South Jakarta. A survey method was employed, distributing questionnaires to a number of employees selected through purposive sampling. The collected data was then analyzed using Structural Equation Modeling Partial Least Square (SEM PLS) method. The research findings indicate that: (1) agility does not show a significant effect on organizational commitment; (2) cyberloafing behavior has a significant influence on organizational commitment; (3) empowerment also demonstrates a significant effect on organizational commitment; (4) work stress does not moderate the relationship between agility and organizational commitment; (5) work stress does not moderate the relationship between cyberloafing behavior and organizational commitment; and (6) work stress does not moderate the relationship between empowerment and organizational commitment .